2017
DOI: 10.17816/ov10110-16
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D and matrix metalloproteinases-2, -9 level in patients with primary open angle glaucoma and pseudoexfoliative glaucoma/syndrome

Abstract: Aim. To determine serum 25(OH)D and plasma MMP-2 and MMP-9 levels in patients with primary open-angle glaucoma (POAG), pseudoexfoliation glaucoma (PEG), and pseudoexfoliation syndrome (PES) - to assess potential associations between vitamin D status and these diseases. Methods. We included 238 patients (105 males and 133 females) aged from 55 to 75 years. One hundred twenty two patients had PEG, 46 patients had POAG, 32 had PES. 38 subjects were healthy, and were considered as the control group. Cases with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous studies agreed with our results and showed that the age-matched controls had a considerably greater amount of 25-OHD than the POAG. According to two investigations, agematched controls had higher serum levels of 1a, 25-dihydroxyvitamin than POAG patients did (13,14).…”
Section: Despitementioning
confidence: 99%
“…Previous studies agreed with our results and showed that the age-matched controls had a considerably greater amount of 25-OHD than the POAG. According to two investigations, agematched controls had higher serum levels of 1a, 25-dihydroxyvitamin than POAG patients did (13,14).…”
Section: Despitementioning
confidence: 99%